PENGAJARAN MUSIK DI SD MELALUI KEGIATAN PENGALAMAN MUSIK - Nurhenti D.s, (Pendidikan Sekolah Dasar, 2011)
Music is one source of beauty and the source of the creation of imaginative experience in children. One method of learning the art of music that can be done is through music experiences. This form of music experience will provide meaningful experiences for children in the art appreciate the music itself. There are several types of activity of musical experience that can be applied in learning the art of music in primary schools, namely listening activities, the activities of singing, playing musical activities, events move to the music, and reading music. The five types of real music experience for elementary students in order to improve and develop the appreciation, empathy, and intuition child music. Arts education in this case the music has not run optimally, as most primary schools do not have a special teacher of art, and this lesson can be said is complete only.